PELAKSANAAN ROYA MELALUI SISTEM ELEKTRONIK TERHADAP HAK TANGGUNGAN AKIBAT KREDIT MACET DI KANTOR PERTANAHAN KABUPATEN BATANG - Fenti Anita Sari; Fitika Andraini (Fakultas Hukum Universitas Stikubank, 2021)
Permen ATR/BPN 9/2019 is a provision regarding the implementation of roya electronically so that registration and deletion of roya can be reached easily, quickly, simply and at low cost. Roya which is done manually is different from electronic. The difference is that the file from the applicant is scanned and registered through the website and is directly corrected by the roya executor, not through the land counter. So that the Notary/PPAT does not have to come to the Land Office. After obtaining the certificate of land rights then it is given back to the certificate holder in this case is the creditor. If the deletion and registration of roya electronically has not been carried out even though the debt has been paid off, the land title certificate still contains a barcode record of encumbrance of Mortgage Rights. Based on the above, how is the implementation of the elimination of Roya Mortgage Electronically at the Land Office of Batang Regency? And what are the Inhibiting and Supporting Factors in the Implementation of Electronic Mortgage Elimination at the Land Office of Batang Regency?. The research method that will be used in this paper is a sociological juridical research method. The approach that the author uses in this study is a sociological juridical approach. The sociological juridical approach emphasizes research that aims to obtain legal knowledge empirically by going directly to the object. The implementation of the abolition of roya with the HT-el System at the Land Office of Batang City has not all been carried out in accordance with the procedures stated in the Technical Guidelines for HT-el. Application files that do not comply with procedures are known from the results of the inspection of the Land Office, if not checked, the HT-el certificate will be issued automatically on the seventh day. Issuance without any inspection from the Land Office if there is a procedural error, it is feared that it will become a problem in the future. Obstacles in HT registration with the HT-el System occur in PPAT, Banks as creditors and the Land Office. This obstacle arises during the HT registration process, both technically and non-technically. The electronic roya removal is carried out by the applicant, namely the debtor, proxy or representative by filling out an electronic application. If seen in practice, the Elimination of Roya electronically electronically or online is carried out through PPAT intermediaries at the PPAT office because PPAT who has a user name and password when accessing the registration system for the Elimination of Roya electronically in order to serve the needs of the community for the Elimination of Roya electronically through the online system still has both external and internal constraints. Keywords: Deletion, Roya, Online